2021
DOI: 10.1111/jocn.15633
|View full text |Cite
|
Sign up to set email alerts
|

Predictor of self‐efficacy in individuals with chronic disease: Stress‐coping strategies

Abstract: Aims and Objectives This study aims to investigate the relationship between stress‐coping strategies of individuals with chronic diseases and their self‐efficacy. Background Self‐efficacy and coping with stress in chronic diseases affect the course of the disease. Design The sample of this methodological study consisted of 178 patients who were hospitalised in a university hospital between November 2017 and November 2018. Methods Data were collected by the face‐to‐face interview method using a Patient Informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
0
8
0
1
Order By: Relevance
“…The findings showed that self-care confidence proved to be an independent predictor of the maintenance and management of self-care. Other studies 18,34,37 have also found significant relationships for the determinant of confidence, which is a key element in the proper performance of self-care. This may be a consequence of the individual's confidence in their knowledge and skills in analyzing situations and making an assertive decision and actively participating in care even in the presence of possible limitations, 18,37 and for this reason, systolic elevated blood pressure may negatively affect this sense of self-control.…”
Section: Discussionmentioning
confidence: 89%
“…The findings showed that self-care confidence proved to be an independent predictor of the maintenance and management of self-care. Other studies 18,34,37 have also found significant relationships for the determinant of confidence, which is a key element in the proper performance of self-care. This may be a consequence of the individual's confidence in their knowledge and skills in analyzing situations and making an assertive decision and actively participating in care even in the presence of possible limitations, 18,37 and for this reason, systolic elevated blood pressure may negatively affect this sense of self-control.…”
Section: Discussionmentioning
confidence: 89%
“…The person's coping mechanisms can be impacted by self-efficacy (Bakan & Inci, 2021). Hadi Kurniyawan et al ( 2022) found a strong and positive association (r = 0.673) between self-efficacy and coping strategy, demonstrating that the higher the patient's self-efficacy, the better their coping strategy will be.…”
Section: Effect Of Self Efficacy On Quality Of Life Through Coping Me...mentioning
confidence: 99%
“…Individuals tend to believe that their actions that can be achieved make a difference. Self-efficacious people are motivated, adept at setting personal goals, and able to apply coping skills to efficiently handle stress and issues (Bakan & Inci, 2021;Suwanti et al, 2019).…”
Section: Effect Of Self Efficacy On Quality Of Life Through Coping Me...mentioning
confidence: 99%
“… 21 Self-efficacy is important for better PSA. 22 Based on previous theories and studies, when women have BC treated with AET, they will adopt either a positive or negative attitude and behaviour to face it, which results in the changes of emotional dimension, self-cognition, self-image and social dimension. After an extensive literature review, no effective questionnaire was found that revealed the PSA of women with BC undergoing AET among the few studies available regarding the psychosocial adjustment of patients with BC.…”
Section: Introductionmentioning
confidence: 99%
“…BCS with an optimistic disposition, and with a positive perception of illness have better health-related quality of life 21. Self-efficacy is important for better PSA 22. Based on previous theories and studies, when women have BC treated with AET, they will adopt either a positive or negative attitude and behaviour to face it, which results in the changes of emotional dimension, self-cognition, self-image and social dimension.…”
Section: Introductionmentioning
confidence: 99%